TINJAUAN BUDAYA ATAS KULTUR TASAWUF BERBASIS MURSYID PEREMPUAN - Mustofa, Mustofa (UIN Maliki Malang, 2009)
Male and female, basically, have the same chance as idol muttaqin person, as well as a leader in the earth, including becoming a teacher of tarekat (mursyid). Assigning female as mursyid will not reduce or break the identity of the Sufism group, on the other hand, it is a kind of glorifying and respecting to the God. However, in tasawuf culture, most of the rituals conducted by the followers often reflecting the God in the male form. This conception, then, influences the way they lead the group. The common way of practicing the leadership model finally drives into legalizing the male superiority as the mursyid rather than the female one. Because of the phenomenon, the paper is written, to explore the issues on male and female role in the Sufism, specifically, for becoming the mursyid. It is expected to be powerful and meaningful cultural analysis which is viewed from tasawuf paradigm.